Contemporary Australian Motherhood Memoir as Personal, Creative, and Political Narrative - Garlick, Lynn (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
In 2010, Elizabeth Podnieks and Andrea O’Reilly published Textual Mothers/ Maternal Texts: Motherhood in Contemporary Women’s Literatures, which examines “how mothering and being a mother are political, personal, and creative narratives unfolding within both the pages of a book and the spaces of a life” (3). O’Reilly further calls on memoirs to not only challenge but to change patriarchal motherhood and to move from “rant to revolution” (“The Motherhood Memoir” 209). Drawing impetus from Podnieks and O’Reilly, I examine selected Austra- lian contemporary motherhood memoirs published since 2010 as literary texts to show that this personal writing is flourishing in new political and creative ways. These narrative examples challenge perceived notions of motherhood and redefine maternal roles, often from a position that intersects the personal and professional. Experiments with genre and style also become political acts to rewrite mother bodies and stories.